PENERAPAN BAURAN PEMASARAN DALAM USAHA MENINGKATKAN VOLUME PENJUALAN PADA CV. SURYA GEMILANG MOTOR LAMONGAN - Ahmadi, Edy Anas (Jurnal Manajemen Dan Akuntansi Medan, 2022)
Application Marketing Mix In The Business Volume Increase Sales By Surya Gemilang Motor Dealer Lamongan. In the business world, where human knowledge is increasingly pushing their increasingly sharp competition, that requires every company to more actively market their goods or their products in the market. Marketing management should be able to create a satisfactory service to customers and at the same time can also compete aktif.Tujuan study was to determine the role of marketing mix ie product, price, promotion, distribution in increasing the volume of motorcycle sales in CV.SuryaGemilang Motor this Lamongan.penelitian using multiple regression analysis and hypothesis testing (test T and F) with Likert scale. The population was 1,299 consumers with a sample of 93 responden.Berdasarkan methods nonpurposivesampling.Hasil simultaneous testing showed a variable product, price, promotion and distribution of jointly significant effect on the sales volume in CV.SuryaGemilang Motor Lamongan with Fhitung 89.839 .with using partial test shows the product variable (X1) of 1,489, the price (X2) is 2,626, promotions (X3) of 2,511 and distribution (X4) of 1.345. Variable price (X2) and promotion (X3) had a partial effect on the volume of sales, product variables (X1) and distribution (X4) does not have a partial effect on the volume penjualan.Dan price variable (X2) were dominant influence on the sales volume of bicycles motorcycle.